Uso da água no Brasil: O papel do efeito tecnológico - Jaqueline Coelho Visentin; Leonardo Szigethy (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Between 2013 and 2016, several regions in Brazil suffered from some event of scarcity, drought and/or the possibility of water rationing. However, the direct abstraction of Blue Water for consumptive use grew 6.38% in the period. In turn, technology is considered an increasingly important factor for the sustainable use of natural resources. In this context, the objective of this article is to investigate the role of the technological effect on variations in the volume of water used in Brazil between 2013 and 2017. To meet this objective, environmentally extended input-output matrices and Structural Decomposition Analysis are used. Among the main results, it is highlighted that the technological effect has not contributed to counteract the pressure for the growth of water use in general. From this type of identification, the proposed method can generate useful information for public policies towards the sustainable use of water.
Keywords: Q25; R15; Q55; 330; technological effect; water; input-output